Development of green synthesised AgNPs decorated on MWCNT modified guar gum-based self-healing hydrogel for strain sensors - Aamir Khan; Nichakan Nichakornpong; Tawan Wongsalam; Peerawat Prathumrat; Chutiwat Likitaporn; Pornnapa Kasemsiri; Manunya Okhawilai (Scientific Reports, 2024)
Abstract Flexible conductive hydrogel strain sensors are gaining popularity due to their exceptional stretchability, sensitivity, and potential for wearable devices. However, their widespread use is hindered by significant issues, such as poor electrical conductivity and weak response time. To address these challenges, new hydrogels based on guar gum, borax, and glycerol have been fabricated via a green synthesis technique. These hydrogels were reinforced with functionalised multiwalled carbon nanotubes (f-MWCNTs) and silver nanoparticle decorated multiwalled carbon nanotubes (AgNP-MWCNTs). The resulting conductive hydrogels exhibited a self-healing capability of 83.2% and effective strain sensing with a gauge factor of 6.58. The incorporation of AgNP-MWCNTs significantly improved the electrical conductivity up to 3.05 ± 0.02 S m− 1, thanks to the tunnelling effect between f-MWCNTs and the synergic interaction of AgNP-MWCNTs. Moreover, the hydrogel sensors displayed excellent durability, enduring 3000 cycles of tensile loading and unloading at 50% strain. This innovative use of green design principles offers a straightforward, cost-effective, and environmentally friendly process for producing high-performance soft materials. These materials hold significant promise for various practical applications, including artificial skins, flexible electronics, and healthcare monitoring, highlighting the high relevance and impact of this research.